2019
DOI: 10.1002/macp.201900147
|View full text |Cite
|
Sign up to set email alerts
|

Anionic Hybrid Copolymerization via Concurrent Oxa‐Michael Addition and Ring‐Opening Polymerizations

Abstract: Here, a new type of anionic hybrid copolymerization is exploited via the concurrent oxa‐Michael addition of ethylene glycol and neopentyl glycol diacrylate and the ring‐opening polymerization of ε‐caprolactone. The hybrid copolymerization process and the resulting copolymers are characterized using nuclear magnetic resonance, size exclusion chromatography, differential scanning calorimetry measurements, and thermogravimetric analysis. The results show that the hybrid copolymerization can proceed smoothly under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Finding an easy method that combines the advantages of both resins for antifouling coatings is the main aim of the present work. For this purpose, hybrid copolymerization of vinyl monomers and lactones seems to be a feasible method. However, the high price of the catalysts has currently hindered their mass production. Here, we designed a type of highly branched copolymer used for self-polishing antifouling coatings, in which the primary chains are composed of methyl methacrylate (MMA) fragments, and the bridges linking two poly­(methylmethacrylate) (PMMA) chains are poly-ε-caprolactone (PCL) fragments (Scheme ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Finding an easy method that combines the advantages of both resins for antifouling coatings is the main aim of the present work. For this purpose, hybrid copolymerization of vinyl monomers and lactones seems to be a feasible method. However, the high price of the catalysts has currently hindered their mass production. Here, we designed a type of highly branched copolymer used for self-polishing antifouling coatings, in which the primary chains are composed of methyl methacrylate (MMA) fragments, and the bridges linking two poly­(methylmethacrylate) (PMMA) chains are poly-ε-caprolactone (PCL) fragments (Scheme ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Simultaneous copolymerization via different mechanisms is an intriguing strategy for synthesizing highly functional polymer materials. In particular, copolymers with different types of monomers can be obtained without cumbersome multistep reactions involving purification and isolation. For example, a diblock copolymer of ε-caprolactone (CL) and styrene was produced in one pot via simultaneous (but orthogonal) living coordination ring-opening polymerization (ROP) and nitroxide-mediated radical polymerization using a bifunctional initiator with initiating sites for both polymerizations .…”
mentioning
confidence: 99%
“…A specific type of this method in which different mechanisms proceed nonorthogonally has the potential to produce copolymers that are otherwise difficult to obtain. This class of copolymerization includes the copolymerization of vinyl monomers and cyclic monomers via the concurrently occurring vinyl-addition and ring-opening mechanisms and chain- and step-growth copolymerization. , These polymerizations are effective for the synthesis of multiblock-type copolymers via two-way crossover reactions. A wider variety of copolymer sequences and architectures can be produced via this type of copolymerization by completely different intermediates or mechanisms, , because the relative rates of both reactions are tuned independently by changing the reaction conditions, such as the amount of catalyst and the solvent polarity.…”
mentioning
confidence: 99%
“…However, amide is rarely employed as a Michael donor for this reaction due to its poor nucleophilicity. Our previous work showed that hydroxy group, another poor nucleophilic group, could be successfully realized in the oxa-Michael addition by the use of PB as catalyst under mild conditions. Inspired by this work, we turned our attention to the Michael addition of amide with acrylamide or acrylate. Herein, propionamide (PA) and N , N -dimethylacrylamide (DMA) were first employed as the Michael donor and acceptor, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%